Comparative Evaluation of Forced Swim Test and Tail Suspension Test as Models of Negative Symptom of Schizophrenia in Rodents. (12th January 2012) - Chatterjee, Manavi; Jaiswal, Manoj; Palit, Gautam
Abstract : Previous studies have shown that the administration of NMDA antagonist can induce negative symptoms of schizophrenia which can be tested through the enhanced immobility observed in the forced swim test (FST). In the present study, we have compared the effects of acute as well as chronic administration of a noncompetitive NMDA receptor antagonist, ketamine on FST, and another behaviour despair model, tail suspension test (TST). Our observations suggest that chronic ketamine administration induced a state of enhanced immobility in FST, but such findings were not replicated in the TST model. Further, in FST, treatment with clozapine reverses the ketamine-induced immobility in mice, whereas it enhances the immobility duration in the TST model. However, haloperidol showed no protective effects in both models. The data suggests that although both of these tests show common behavioural measure of feeling despair, however, the underlying pathophysiology seems to be different. Hence, forced swim test but not tail suspension test can be used as a model of negative symptom of psychosis in mice.